An Updated Meta-Analysis for Safety Evaluation of Alirocumab and Evolocumab as PCSK9 Inhibitors - Hye Duck Choi; Ji Hae Kim (Cardiovascular Therapeutics)
Background. Alirocumab and evolocumab, as protein convertase subtilisin kexin type 9 (PCSK9) inhibitors, have been reported to reduce cardiovascular risk. This meta-analysis is aimed at updating the safety data of PCSK9 inhibitors. Methods. We assessed the relative risk for all treatment-related adverse events, serious adverse events, diabetes-related adverse events, and neurocognitive and neurologic adverse events with PCSK9 inhibitors compared to controls (placebo or ezetimibe). In addition, we conducted a meta-analysis to quantitatively integrate and estimate the adverse event rates in long-term studies. Results. There were no significant differences between PCSK9 inhibitors and controls in the relative risk analysis. In a subgroup analysis of each PCSK9 inhibitor, alirocumab treatment significantly reduced the risk of serious adverse events compared to control treatment (risk ratio RR=0.937; 95% confidence interval (CI), 0.896–0.980), but no significant difference was observed with evolocumab treatment (RR=1.003; 95% CI, 0.963–1.054). Moreover, alirocumab treatment afforded a significant reduction in the risk of diabetes-related adverse events compared to control treatment (RR=0.9137; 95% CI, 0.845–0.987). The overall incidence (event rate) of long-term adverse events was 75.1% (95% CI, 71.2%–78.7%), and the incidence of serious long-term event rate was 16.2% (95% CI, 11.6%–22.3%). Conclusions. We suggest that alirocumab and evolocumab are generally safe and well tolerated and that their addition to background lipid-lowering therapy is not associated with an increased risk of adverse events or toxicity.